2016
DOI: 10.1111/zph.12308
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Resistance to Disinfectants and Antibiotics in Methicillin‐Resistant Staphylococcus aureus Strains Isolated from Pigs

Abstract: The aim of this research was to study the phenotypic resistances to disinfectants and antibiotics in strains of methicillin-resistant Staphylococcus aureus (MRSA) obtained from Canary black pigs. Analyses were performed on 54 strains of MRSA, isolated in Canary black pigs from the province of Tenerife (Spain); all of them carried the mecA gene. The strains were isolated by means of nasal swab samples of healthy pigs, collected under veterinarian supervision. Bactericidal activity of antiseptics and disinfectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…All MRSA strains isolated were resistant to cefoxitin, penicillin and ampicillin, a finding in agreement with the report that MRSA isolates are usually resistant to βlactams [4,37]. Similarly, a high frequency of resistance (88.9%) was detected to tetracycline amongst MRSA strains in our study, a finding in agreement with published reports [37,38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All MRSA strains isolated were resistant to cefoxitin, penicillin and ampicillin, a finding in agreement with the report that MRSA isolates are usually resistant to βlactams [4,37]. Similarly, a high frequency of resistance (88.9%) was detected to tetracycline amongst MRSA strains in our study, a finding in agreement with published reports [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…All MRSA strains isolated were resistant to cefoxitin, penicillin and ampicillin, a finding in agreement with the report that MRSA isolates are usually resistant to βlactams [4,37]. Similarly, a high frequency of resistance (88.9%) was detected to tetracycline amongst MRSA strains in our study, a finding in agreement with published reports [37,38]. The high frequency of resistance exhibited to by MRSA strains to penicillin, ampicillin, streptomycin and tetracycline in our study may be attributed to their frequent use in veterinary practice in the country [16].…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the pig raising environment, the stringency of the ultraviolet radiation that has a certain bactericidal effect and results in the decrease of bacteria in the pigpen in summer ( Baubinas et al, 1983 ; Kraemer et al, 2018 ). On the other hand, the high temperature in summer strengthens disease prevention and control, especially using much more antibiotics to reduce the production of bacteria to some extent ( Espigares et al, 2017 ; Johnson et al, 2017 ). Although there is no direct evidence linking microbial diversity in summer boar semen to antibiotic use, the high dosage utilization of antibiotics can alter the composition of gut microbes in pigs ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory-based adaptation experiments have shown that step-wise exposure of initially susceptible bacteria to subinhibitory concentrations of benzalkoniumchloride, chlorhexidine, triclosan and some commercial disinfectants may lead to decreased susceptibility to either antibiotics or disinfectants [69]. Recent studies investigated the disinfectant susceptibility of bacteria isolated from live-stock and its environment [1014] or evaluated the correlation [2, 15] or association [16] between antibiotic resistance and a decreased susceptibility to disinfectants. However, in marked contrast to the in vitro reports, no evidence that the use of disinfectants selects for antimicrobial resistance under practical conditions was found.…”
Section: Introductionmentioning
confidence: 99%